2014
DOI: 10.1155/2014/673939
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Light Technologies for Reducing Microbial Populations in Liquid Suspensions

Abstract: The aim of the current study was to evaluate the effectiveness of three nonthermal light technologies (NUV-Vis, continuous UV, and HILP) on their ability to inactivate Escherichia coli K12 and Listeria innocua.   E. coli K12 was selected as a representative microorganism for the enterohaemorrhagic foodborne pathogen E. coli O157:H7 and L. innocua as a surrogate microorganism for the common foodborne pathogen Listeria monocytogenes, respectively. The liquid matrix used for the disinfection experiments was a liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In many cases complete removal of bacterial populations was obtained. These results are agree with those of Birmpa et al [6] which confirm that visible light particularly at wavelengths of 405 nm is effective in inactivating gram-positive and gram-negative bacteria species and antibiotic-resistant microorganisms. The effect in the study could be due to changes in the membrane permeability of the irradiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…In many cases complete removal of bacterial populations was obtained. These results are agree with those of Birmpa et al [6] which confirm that visible light particularly at wavelengths of 405 nm is effective in inactivating gram-positive and gram-negative bacteria species and antibiotic-resistant microorganisms. The effect in the study could be due to changes in the membrane permeability of the irradiated cells.…”
Section: Discussionsupporting
confidence: 93%
“…Kim et al [40] studied the inactivation of E. coli and Salmonella enterica on fresh cut mango by 405 nm LED treatment, where 36 h treatment resulted in cell count reductions of 1 log CFU/cm 2 with a maximum dose of 3.6 kJ/cm 2 . E. coli K12 was susceptible to 395 nm LED in a dose-dependent manner [25]. However, only few studies reported the use of LED treatment in low-a w foods.…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis (Endarko and others ). Several authors posit that Gram‐positive bacteria are more susceptible than Gram‐negative species (Maclean and others ; Birmpa and others ), whereas others posit that susceptibility is not determined by Gram nature, but nonetheless varies greatly among different species (Ghate and others ). Within species, it was found that there were differences in susceptibility between Campylobacter spp.…”
Section: Leds In Food Safetymentioning
confidence: 99%